Analysis of the total wastage of blood bags and various blood components in a blood bank of a tertiary care hospital - Kori, Shivkumar; Yadav, Yogesh R.; Banerjee, Sujata; Bari, Vaibhav (International Journal Of Community Medicine And Public Health, 2024)
Background: Majority of the medical and surgical emergency procedures being dependent on Blood and blood components, it has played a vital role in patient management. This enlightens the importance and need of proper utilization of blood and its components by ensuring minimal wastage. Aim was to determine the percentage of blood and blood component wastage in a blood bank of a tertiary care hospital. Methods: A retrospective study of donors from January 2015 to December 2020 was done in a blood bank of a tertiary care hospital located in western Maharashtra. Results: Out of the total blood bags collected, 411 (2.8%) blood bag units were discarded due to seropositivity, 373 whole blood bags and 2588 platelet bags had to be discarded. The most common reason for discard of platelet bags were due to expiry; 1789 FFP (fresh frozen plasma) bags, 131 bags of PRBC (packed red blood cells), 85 bags of plasma and 235 cryoprecipitate bags were discarded due to various reasons. Conclusions: Blood being an irreplaceable and important resource, needs to be properly utilized and ideally zero percent wastage should be encouraged. Training programmes for doctors on usage of blood / blood components is highly recommended.